The study of intestinal toxicity induced by gossypol acetic acid and the mechanism using zebrafish model and network toxicology - Hanxue Zhao; Yuxin Wang; Guoliang Zhang; Yudi Jing; Fangzhen Li; Xiqiang Chen; Kechun Liu; Guiling Chen; Rongchun Wang (Toxicology and Applied Pharmacology, 2026)

Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

Water-level elevation governs iron-bound organic carbon dynamics in a reservoir drawdown zone - Haojun Deng; Zhuangpeng Zheng; Zhi Zhang; Aimin Chen; Guiling Lin (Journal of Soils and Sediments, 2026)

ETV5 upregulates PD-L1 transcription to inhibit cytotoxic CD8+ T cell proliferation in colorectal cancer - Fei Kuang; Zhongwen Hu; Longtao Huangfu; Guiling Yan; Swati Dhiman; Wenzheng Chen; Ziyu Li (Science China Life Sciences, 2026)

The influence of PIK3R1 and its phosphorylation on the transplantation immunity of Pinctada fucata martensii - Guiling Yin; Jie Chen; Haiying Liang; Lining Ma; Runlin Lei (Aquaculture, 2026)

Differences in Volatile Composition and Expression of Genes Involved in Terpenes Biosynthesis in Hemerocallis Species - Wenjie Gao; Yuyang Li; Xingran Kou; Qinfei Ke; Feng Chen; Guiling Liu; Qingran Meng (Journal of Plant Growth Regulation, 2026)

Bacillus subtilis as a powerful weapon in the removal of environmental pollutants - Mingqiu Liu; Wen-Juan Chen; Guiling Si; Chenxi Yan; Haoran Song; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Biodegradation of the widely used amide herbicides: Microbial resources, catabolic pathways and molecular mechanisms - Guiling Si; Quanhong Zhang; Mingqiu Liu; Wen-Juan Chen; Yuting Tong; Parul Chaudhary; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

Raindrop size distribution characteristics of summer and autumn tropical cyclones in the South China Sea based on satellite observations - Guiling Qian; Jiangnan Li; Jianfei Chen (Dynamics of Atmospheres and Oceans, 2025)

Petrological and geochemical insights into the genesis and geothermal potential of Late Neoarchean granitoid rocks in the Matouying Uplift, North China Craton - Quan Gan; Luming Song; Shuantong Shangguan; Xiaofei Qi; Zhiwei Liao; Jianye Chen; Zhili Yang; Guiling Wang; Guangyao Xin; Chongyuan Zhang (Precambrian Research, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Genetically engineered Bacillus subtilis-derived extracellular vesicles Alleviates Ulcerative colitis by restoring intestinal barrier and regulating gut microbiota - Jiali Chen; Chaozhi Wei; Chunqiang Pan; You Wei; Baoxian Li; Tao Liu; Xiao Wang; Zhengshun Wen; Yao Zhao; Mengyu Zhang; Jintao Cheng; Yuanxiang Jin; et al. (Chemical Engineering Journal, 2025)

Unveiling the hydrolase Oph2876 mediated chlorpyrifos degradation mechanism in Pseudomonas nitroreducens and its potential for environmental bioremediation - Haoran Song; Wen-Juan Chen; Shao-Fang Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Hazardous Materials, 2025)

Removal of alachlor from the water/soil environments: The significance of microbial remediation and its biochemical mechanisms - Zeren Li; Mengyi Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Water Process Engineering, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

Removal of environmental pollutants using biochar: current status and emerging opportunities - Haoran Song; Shao-Fang Chen; Guiling Si; Kalpana Bhatt; Shao-Hua Chen; Wen-Juan Chen (Environmental Geochemistry and Health, 2024)

First record of the sap beetle Phenolia picta invading Eastern honey bee (Apis cerana) (Hymenoptera, Apidae) colonies - Lin Du; Wenbin Liu; Xiaoshun Chen; Jinge Licao; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Exploring the dynamic behaviors of five pesticides in lettuce: Implications for consumer health through field and modeling experiments - Yanhua Wang; Panpan Liu; Guiling Yang; Fang Shu; Chen Chen (Food Chemistry, 2024)

Preparation and identification of antioxidant peptides from Quasipaa spinosa skin through two-step enzymatic hydrolysis and molecular simulation - Daren Wu; Yuanhao Cao; Dejin Su; Emad Karrar; Lingyu Zhang; Chaoxiang Chen; Ning Deng; Zhengxiao Zhang; Jingwen Liu; Guiling Li; Jian Li (Food Chemistry, 2024)

High variation of worker cell and morphology between two adjacent populations of honey bee, Apis cerana (Hymenoptera, Apidae) - Rui Zhu; Weilai Zhong; Yuhui Chen; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Ecological transitions in Xinjiang, China: Unraveling the impact of climate change on vegetation dynamics (1990–2020) - Haichao Hao; Junqiang Yao; Yaning Chen; Jianhua Xu; Zhi Li; Weili Duan; Sadaf Ismail; Guiling Wang (Journal of Geographical Sciences, 2024)

Synthesis of Mn/Cu co-doping mesoporous carbon by template method for gas phase mercury removal - Ruhao Gong; Haihui Chen; Xiuya Rao; Jihong Chi; Ziqi Zhang; Guiling Xu; Dandan Chen; Qiang Zhou; Ping Lu (Fuel, 2024)

Selective extraction of lithium ions by phosphoroxy-functionalized ionogels from the mother liquor of Li2CO3 - Yuhong Huang; Xiaowei Li; Guiling Luo; Duanjian Tao; Linlin Chen; Jing Sun; Bizuneh Kaleab; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2024)

A review of cumulative risk assessment of multiple pesticide residues in food: Current status, approaches and future perspectives - Mengxue Yang; Yihan Wang; Guiling Yang; Yanhua Wang; Fengquan Liu; Chen Chen (Trends in Food Science & Technology, 2024)

Coupled THMC modeling on chemical stimulation in fractured geothermal reservoirs - Haoran Xu; Guihong Liu; Zhihong Zhao; Feng Ma; Guiling Wang; Yuedu Chen (Geothermics, 2024)

Vitamin a supplementation during pregnancy in shaping child growth outcomes: A meta-analysis - Guiling Ma; Yanting Chen; Xiangdong Liu; Yao Gao; Jeanene M. Deavila; Mei-Jun Zhu; Min Du (Critical Reviews in Food Science and Nutrition, 2023)

The spatial patterns and driving mechanisms of blue carbon ‘loss’ and ‘gain’ in a typical mangrove ecosystem: A case study of Beihai, Guangxi Province of China - Zhenxi Xie; Haonan Li; Yuan Yuan; Wei Hu; Gang Luo; Longtian Huang; Mo Chen; Weimei Wu; Guiling Yan; Xiang Sun (Science of The Total Environment, 2023)

Identification of flavonoids in Anoectochilus roxburghii and in vitro inhibition of key enzymes relevant to metabolic syndrome - Jiahao Yuan; Xiuna Wu; Emad Karrar; Lingyu Zhang; Jingwen Liu; Guiling Li; Chaoxiang Chen; Zhengxiao Zhang; Daren Wu; Jian Li (Food Bioscience, 2023)

Associations between environmental heavy metals exposure and preserved ratio impaired spirometry in the U.S. adults - Chen Chen; Shunan Zhang; Ting Yang; Chen Wang; Guiling Han (Environmental Science and Pollution Research, 2023)
We examined 9556 individuals aged 18 to 79 years who had information on spirometry testing and heavy metals and used multivariable logistic or linear regression to evaluate associations between serum levels of cadmium, lead, and mercury and PRISm and lung function in U.S. adults, which were conducted first in all participants, and then separately in never/former smokers and current smokers. The overall prevalence of PRISm was 7.02%. High levels of serum cadmium were significantly associated with PRISm in all individuals, no matter in never/former smokers (quartile 4 vs 1, the OR = 2.517, 95% CI = 1.376–4.604, p -trend = 0.0077) and current smokers (quartile 4 vs 1, the OR = 2.201, 95% CI = 1.265–3.830, p -trend = 0.0020). Serum lead and mercury were not significantly correlated with PRISm, regardless of smoking status. Serum cadmium was strongly correlated with lower FEV 1 /FVC, regardless of smoking status. Besides, serum cadmium was also significantly related to lower FVC % predicted in never/former smokers and lower FEV 1 % predicted in current smokers. Serum lead was strongly correlated with lower FVC % predicted and FEV 1 /FVC in all individuals and never/former smokers. And serum mercury was significantly associated with decrements in FVC % predicted in all individuals and current smokers. These findings demonstrate that serum cadmium is associated with a higher risk of PRISm and lower lung function, with the most significant effect on FEV 1 /FVC in particular. Our results also indicate that exposure to lead and mercury negatively affects lung function in never/former smokers and current smokers, respectively.

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Breaking intramolecular hydrogen bonds of polymer films to enable dendrite-free and hydrogen-suppressed zinc metal anode - Yiyang Mao; Zhuo Li; Yiju Li; Dianxue Cao; Guiling Wang; Kai Zhu; Guohua Chen (Chemical Engineering Journal, 2023)

Electrochemical lithium ion pumps for lithium recovery: A systematic review and influencing factors analysis - Guiling Luo; Xiaowei Li; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Desalination, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

G-CSF promotes the viability and angiogenesis of injured liver via direct effects on the liver cells - Zifeng Liu; Guiling Zhang; Jing Chen; Jingjing Tong; Hongmin Wang; Jing Chen; Dong Yang; Jinhua Hu (Molecular Biology Reports, 2022)
Background Presently, liver transplantation is the only treatment strategy for liver failure (LF). Although granulocyte-colony stimulating factor (G-CSF) exhibits protective functions in LF, it is not clear whether it directly affects the liver cells. Methods and Results We established an injured liver cell model and observed that G-CSF treatment promoted cell viability and enhanced Ki67 and VEGF-A expression. Thereafter, human umbilical vein endothelial cells (HUVECs) were cultured in a conditioned medium collected from the G-CSF-treated injured liver cells. HUVECs’ proliferation and tubule formation were promoted. Furthermore, in an injured liver mouse model, confirmed via haematoxylin–eosin staining, we evaluated serum alanine aminotransferase activity, Ki67 expression, and microvessel density (MVD). G-CSF treatment significantly relieved liver injury, upregulated Ki67 expression, and enhanced MVD in the injured mouse liver tissue. Additionally, AKT and ERK signal targets were explored, and it was demonstrated that the effects of G-CSF on injured liver cells were mediated through the AKT and ERK signalling pathways. Conclusions G-CSF promotes injured liver viability and angiogenesis by directly affecting injured liver cells via the AKT and ERK signalling pathways. These findings improve our understanding of the role of G-CSF in recovery from LF.

Sensitivity of Typhoon Lingling (2019) simulations to horizontal mixing length and planetary boundary layer parameterizations - Siqi Chen; Feng Xu; Yu Zhang; Guiling Ye; Jianjun Xu; Chunlei Liu (Frontiers of Earth Science, 2022)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Dissolved Nitrous Oxide and Hydroxylamine in the South Yellow Sea and the East China Sea During Early Spring: Distribution, Production, and Emissions - Xueji Gu; Fang Cheng; Xiaolei Chen; Guanxiang Du; Guiling Zhang (Frontiers in Marine Science, 2021)
Coastal marine systems are active regions for the production and emission of nitrous oxide (N 2 O), a potent greenhouse gas. Due to the inherently high variability in different coastal biogeochemical cycles, the factors and mechanisms regulating coastal N 2 O cycling remain poorly understood. Hydroxylamine (NH 2 OH), a potential precursor of N 2 O, has received less attention than other compounds in the coastal areas. Here, we present the spatial distribution of N 2 O and the first reported NH 2 OH distribution in the South Yellow Sea (SYS) and the East China Sea (ECS) between March and April 2017. The surface N 2 O concentrations in the SYS and the ECS varied from 5.9 to 11.3 nmol L –1 (average of 8.4 ± 1.4 nmol L –1 ) and were characterized by offshore and north–south decreasing gradients. NH 2 OH showed patchy characteristics and was highly variable, fluctuating between undetectable to 16.4 nmol L –1 . We found no apparent covariation between N 2 O and NH 2 OH, suggesting the NH 2 OH pathway, i.e., nitrification (ammonium oxidation), was not the only process affecting N 2 O production here. The high NH 2 OH values co-occurred with the greatest chlorophyll- a and oxygen levels in the nearshore region, along with the relationships between NO 2 – , NO 3 – , and NH 2 OH, indicating that a “fresh” nitrifying system, favoring the production and accumulation of NH 2 OH, was established during the phytoplankton bloom. The high N 2 O concentrations were not observed in the nearshore. Based on the correlations of the excess N 2 O (ΔN 2 O) and apparent oxygen utilization, as well as ΔN 2 O vs. NO 3 – , we concluded that the N 2 O on the continental shelf was mainly derived from nitrification and nitrifier denitrification. Sea-to-air fluxes of N 2 O varied from −12.4 to 6.6 μmol m –2 d –1 (−3.8 ± 3.7 μmol m –2 d –1 ) using the Nightingale et al. (2000) formula and −13.3 to 6.9 μmol m –2 d –1 (−3.9 ± 3.9 μmol m –2 d –1 ) using the Wanninkhof (2014) formula, which corresponds to 75–112% in saturation, suggesting that the SYS and the ECS acted overall as a sink of atmospheric N 2 O in early spring, with the strength weakening. Our results reveal the factors and potential mechanisms controlling the production and accumulation of NH 2 OH and N 2 O in the SYS and the ECS during early spring.

A New Method for Detection African Swine Fever Virus: Time-resolved Fluorescence Immunoassay - Cuicui Chen; Hongrui Lai; Huankun Liang; Ying He; Guiling Guo; Laiqing Li (Journal of Fluorescence, 2021)

Projecting the future vegetation–climate system over East Asia and its RCP-dependence - Weiguang Liu; Guiling Wang; Miao Yu; Haishan Chen; Yelin Jiang; Meijian Yang; Ying Shi (Climate Dynamics, 2020)

Assessing simulated summer 10-m wind speed over China: influencing processes and sensitivities to land surface schemes - Xin-Min Zeng; Ming Wang; Ning Wang; Xiang Yi; Chaohui Chen; Zugang Zhou; Guiling Wang; Yiqun Zheng (Climate Dynamics, 2018)

Identification and characterization of a novel NAC-like gene in chrysanthemum (Dendranthema lavandulifolium) - Yanfang Yang; Kai Zhu; Jian Wu; Liqing Liu; Guiling Sun; Yanbiao He; Fadi Chen; Deyue Yu (Plant Cell Reports, 2016)

Multi-functional Liposomes Enhancing Target and Antibacterial Immunity for Antimicrobial and Anti-Biofilm Against Methicillin-Resistant Staphylococcus aureus - Yansha Meng; Xucheng Hou; Jiongxi Lei; Mengmeng Chen; Shuangchen Cong; Yuanyuan Zhang; Weiming Ding; Guiling Li; Xinru Li (Pharmaceutical Research, 2016)

Joint toxicity of chlorpyrifos, atrazine, and cadmium at lethal concentrations to the earthworm Eisenia fetida - Guiling Yang; Chen Chen; Yanhua Wang; Leiming Cai; Xiangzhen Kong; Yongzhong Qian; Qiang Wang (Environmental Science and Pollution Research, 2015)

Identification of QTLs for salt tolerance at germination and seedling stage of Sorghum bicolor L. Moench - Hailian Wang; Guiling Chen; Huawen Zhang; Bin Liu; Yanbing Yang; Ling Qin; Erying Chen; Yanan Guan (Euphytica, 2014)

Isolation and characterization of ten microsatellite markers of Fenneropenaeus penicillatus - Yuanyu Cao; Zhongbao Li; Guiling Zhang; Xiaojiao Chen; Lina Chen; Qinghui Li (Conservation Genetics Resources, 2012)

ITS sequence-based identification and utilization evaluation of “Nanjiang” (Lonicera similis Hemsl.), a local cultivar in Sichuan, China - Shangqin Hu; Guiling Dong; Xiaomin Chen; Lulin Huang; Xiao Yang; Wen Tong; Linhan Bai (Genetic Resources and Crop Evolution, 2012)

Molecular cytogenetic identification of a novel dwarf wheat line with introgressed Thinopyrum ponticum chromatin - Guiling Chen; Qi Zheng; Yinguang Bao; Shubing Liu; Honggang Wang; Xingfeng Li (Journal of Biosciences, 2012)

Polymorphisms of coding region of BMPR-IB gene and their relationship with litter size in sheep - Mingxing Chu; Lihua Jia; Yingjie Zhang; Mei Jin; Hongquan Chen; Li Fang; Ran Di; Guiling Cao; Tao Feng; Qianqian Tang; Yuehui Ma; Kui Li (Molecular Biology Reports, 2011)